Studi Kasus: Persepsi Dan Pengalaman Mahasiswa Selama Perkuliahan Profesi Kependidikan Secara Daring - Yurni Yurni (Universitas Batanghari Jambi, 2021)
The opinions and experiences of 8 students who took the Education Profession course online were investigated. The data obtained through the focused interview technique were examined using thematic analysis. Students have positive and negative views on several aspects of online learning. Three main factors were found that influence students in online learning: (1) students' social presence, (2) lecturers' teaching competence, and (3) internet network. The findings of this study are expected to improve the practice of online lectures and the quality of teaching and learning in universities.